If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -1 = -5x + 18 Reorder the terms: -1 + -6x = -5x + 18 Reorder the terms: -1 + -6x = 18 + -5x Solving -1 + -6x = 18 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -1 + -6x + 5x = 18 + -5x + 5x Combine like terms: -6x + 5x = -1x -1 + -1x = 18 + -5x + 5x Combine like terms: -5x + 5x = 0 -1 + -1x = 18 + 0 -1 + -1x = 18 Add '1' to each side of the equation. -1 + 1 + -1x = 18 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 18 + 1 -1x = 18 + 1 Combine like terms: 18 + 1 = 19 -1x = 19 Divide each side by '-1'. x = -19 Simplifying x = -19
| 20=14+n | | 4x^2+10=0 | | 11x-9=24 | | 25x^4y^8-5vxy^7=0 | | 5+2(x+4)=3+2x | | 1.3x=7.8 | | 8x+3=39 | | 6x^2=7x-1 | | 5x-1=7x-21 | | 9(2n-1)=(7n+5)+1 | | (x+5-.4)=7(5x+25) | | -4x+1= | | -36=-6(-8+7n)+6(-2n-5) | | 5ln(4x)=20 | | 4(x-6)+2(3x-5)= | | 8-(-8)= | | 5t-9=-3+7 | | 110y+11y=0 | | 3-x=-3 | | 9=6x+3x | | y=4a^2+12a+9 | | 45y+5x=-25 | | -5u=-60 | | 45x+5y=-25 | | 2k+3(k+4)=3 | | -48-12= | | -16=-8x+4(2+5x) | | 49b^2-36= | | -3(5s-5)-15=-2(9s+0)-2 | | -8p^2r-71pr-56r=0 | | x^2-3x-18=10 | | 7+4x-9=-6x |